Phytochemical Screening and Analyses of Eight Selected Heavy Metals in an Air-dried and Sun-dried Leaf of Alternanthera brasiliana (L.) O Kuntze - J. O, Arogbodo; O. A, Ajayi; I. A, Adebayo (International Journal of Scientific Research in Biological Sciences, 2020)
The growing interest in ethno-medicine calls for effective laboratory scrutiny of the part(s) of the medicinal plant(s) being used as raw materials in the preparation of useful products as a way of certifying their bio-safety. To achieve this aim, air-dried and sun-dried leaves of Alternanthera brasiliana (L.) were subjected to preliminary analyses of its phytochemicals and some heavy metals using standard methods. The results confirmed the presence of saponins, tannins, flavonoids, steroids, terpenoids, cardiac glycosides, and absence of phlobatannins, alkaloids, and anthraquinones in both in air-dried (ADS) and sun-dried samples (SDS). The quantity of the phytochemicals were found to be in decreasing order of saponins > terpenoids > steroids > cardic glycosides > flavonoids > Tannins and the heavy metal values also in the order of Fe > Zn > Cu > Mn > Se > Cd > Co > Pb. The heavy metals in the two samples were within the permissible safe limits recommended by Food and Agriculture Organization (FAO) and World Health Organization (WHO); indicating that the leaf of A. brasiliana is not toxic of the analyzed metals. Likewise, it was deduced from the results that air-drying could be a preferred processing method in the preparation of A. brasiliana leaf as more of the phytochemicals and metals were found in the air-dried than the sun-dried leaf sample.